Edu_Vistec : a software for computer vision educational trainer using MATLAB - Law, Kok Sin (2010)
Nowadays, from time to time technologies become more advances that bring much advantage for our human life. But, it needs time for us to learn especially the knowledge about image processing because it uses for many field such as medical or aerospace. So, this project is a study that mains in the basic applications of image processing. It will introduce to the new learner about the image processing. MATLAB software is the main tools that will be use for the application of image processing. MATLAB software has been chosen because of this tool is a universal and all well known tool. Then, MATLAB GUI is one of the parts that use to create the module of those applications. The main outcome of this project is to create a module about the application of image processing for learning purpose. In this module which will cover two parts, which is shape detection and color recognition (RGB). The method that will be use for the shape detection is edge detection. A few edge-finding methods will be used for this application such as Sobel, Prewitt, Roberts, Laplacian of Gaussian (Log), zero-cross and also canny technique. Therefore, the user can learn much in this module. Then, for the application of color part used histogram to recognize the 3 basic colors, that are red, green and blue. To complete this project it need to further study about the MATLAB tools briefly and also all the technique that use to create that module. Finally, this module can give the benefit for the new learner of image processing to more understand about the useful applications. This module was designed to perform basic applications effectively